2003
DOI: 10.2320/matertrans.44.2175
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Board Level Reliability for μBGA Solder Joints Using Underfill

Abstract: The underfilling BGA as an alternative to direct chip attachment for high density packaging technologies have been developed. This paper discusses the thermomechanical and metallurgical effects of underfill material and the resulting improvement in board level reliability for underfilled BGA assemblies. Finite element analysis (FEA) models were developed to predict the thermal fatigue life of the solder joints during thermal cycling tests for BGA assemblies without and with underfill material. FEA predicted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To not only improve adhesion force but also release thermal strain at the interface between a Si chip and Cu pads, underfill materials could be used and they play the role of relaxing the thermal stresses between the interface and the base materials [2,10]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To not only improve adhesion force but also release thermal strain at the interface between a Si chip and Cu pads, underfill materials could be used and they play the role of relaxing the thermal stresses between the interface and the base materials [2,10]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the fatigue life of the solder connections was estimated by the number of thermal cycles that resulted in cracking or failure 50 % of the total solder joints in 10 specimens. 12)…”
Section: Methodsmentioning
confidence: 99%
“…Many thermal fatigue tests on IC packages have been performed. Kim et al 5 found that the introduction of an underfill resin reduced the maximum stress at the solder joint of a ball grid array (BGA) package by approximately 60%, and the fatigue life under a −65°C/150°C thermal cycle was increased by approximately eight times compared with that without the underfill resin. Thus, it was concluded that the underfill resin was effective in improving the connection reliability.…”
Section: Introductionmentioning
confidence: 99%